Applications of fiberglass reinforced composites in dental clinical specialties: systematic review - Morales Lastre, Cristian Camilo (2024)
Objective: To identify and describe the uses of fiberglass-reinforced composites in different dental clinical specialties. Methods: A scientific literature search was conducted in databases such as ScienceDirect, Semantic Scholar, MEDLINE, and EBSCO, during December 2023, using as descriptors the words fiberglass reinforcing composite, fiber-reinforced composite, dentistry, dental applications, dental specialties, combined with the Boolean operators AND and OR. Only original articles, literature reviews, and short communications published from 2018 onwards were included. Results: From the bibliographic search, 15 articles were selected, within which the uses of fiberglass reinforced composites were identified in dental clinical specialties such as endodontics, oral rehabilitation, periodontics, orthodontics, pediatric dentistry, and oral and maxillofacial surgery. Conclusion: Interest in the use of fiberglass-reinforced composites in dentistry is growing because they offer strength and hardness comparable to dental tissues, along with highly satisfactory aesthetics. However, more applications of these should be studied and new types of fiber reinforcement should be investigated.